Method for producing anisotropic magnetic powder, and anisotropic magnetic powder

A two-step nitriding process with controlled atmospheres produces anisotropic magnetic powder with narrow particle size distribution and high residual magnetization, addressing the limitations of existing methods by enhancing magnetic characteristics without mechanical crushing.

JP2025014046AActive Publication Date: 2025-01-28NICHIA CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024191379
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

Existing methods for producing magnetic powder result in wide grain distribution and insufficient magnetic characteristics, particularly for larger particle sizes.

Method used

A two-step nitriding process at controlled temperatures, combined with precise control of oxygen and nitrogen atmospheres, to produce anisotropic magnetic powder with narrow particle size distribution and high residual magnetization.

Benefits of technology

The method achieves magnetic powder with a narrow particle size distribution and high residual magnetization, suitable for applications requiring strong magnetic properties without mechanical crushing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014046000001
    Figure 2025014046000001
  • Figure 2025014046000002
    Figure 2025014046000002
  • Figure 2025014046000003
    Figure 2025014046000003
Patent Text Reader

Abstract

To provide magnetic powder having a narrow particle size distribution and having high residual magnetization, and a method for producing the same.SOLUTION: A method for producing anisotropic magnetic powder comprises: a pretreatment step in which an oxide comprising Sm and Fe is heat-treated in a reducing gas-containing atmosphere to obtain a partial oxide; a step in which the partial oxide is heat-treated in the presence of a reducer to obtain alloy particles; and a step in which the alloy particles are heat-treated at a first temperature of 400°C or more to 470°C or less in a nitrogen or ammonia-containing atmosphere and is thereafter heat-treated at a second temperature of 480°C or more to 610°C or less to obtain a nitride.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing anisotropic magnetic powder and anisotropic magnetic powder. [Background technology]

[0002] Patent Document 1 discloses a SmFeN sintered magnet, and discloses a magnetic powder with a small average particle size and low oxygen content for use in sintering. However, the magnetic powder is produced by pulverizing a magnetic powder with an average particle size of 20 μm or more using a jet mill, and only a powder with a wide particle size distribution can be produced.

[0003] Patent Document 2 discloses a method for producing anisotropic magnetic powders of SmFeN, SmFeLaN, and SmFeLaCoN, and Patent Document 3 discloses a method for producing anisotropic magnetic powders of SmFeN, SmFeLaN, and SmFeWN, respectively. Although the magnetic powders obtained in these patent documents have excellent magnetic properties, magnetic powders with higher remanent magnetization are desired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-55072 A [Patent Document 2] JP 2019-112716 A [Patent Document 3] JP 2020-102606 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a magnetic powder having a narrow particle size distribution and high remanent magnetization, and a method for producing the same. [Means for solving the problem]

[0006] A method for producing an anisotropic magnetic powder according to one aspect of the present invention includes the steps of: A pretreatment step of obtaining a partial oxide by heat-treating an oxide containing Sm and Fe in an atmosphere containing a reducing gas; heat treating the partial oxide in the presence of a reducing agent to obtain alloy particles; and A step of heat-treating the alloy particles at a first temperature of 400° C. to 470° C. in a nitrogen or ammonia-containing atmosphere, and then heat-treating the alloy particles at a second temperature of 480° C. to 610° C. to obtain a nitride. Includes. Effect of the Invention

[0007] In the method for producing anisotropic magnetic powder of the present invention, nitriding is performed at two temperatures, so that anisotropic magnetic powder with a narrow particle size distribution and high remanence can be produced. This is particularly effective in the case of magnetic powder containing La and having a large average particle size. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the embodiments of the present invention will be described in detail. However, the embodiments shown below are examples for embodying the technical idea of ​​the present invention, and the present invention is not limited to the following. In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. Furthermore, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0009] The method for producing the anisotropic magnetic powder of the present embodiment is as follows: A pretreatment step of obtaining a partial oxide by heat-treating an oxide containing Sm and Fe in an atmosphere containing a reducing gas; heat treating the partial oxide in the presence of a reducing agent to obtain alloy particles; and A step of heat-treating the alloy particles at a first temperature of 400° C. to 470° C. in a nitrogen or ammonia-containing atmosphere, and then heat-treating the alloy particles at a second temperature of 480° C. to 610° C. to obtain a nitride. In particular, in the case of oxides having a large particle size, such as oxides containing La, nitriding may not progress sufficiently to the inside of the oxide particles, but by nitriding at two temperatures, the inside of the oxide particles is also sufficiently nitrided, and a magnetic powder with a narrow particle size distribution and high residual magnetization can be obtained.

[0010] [Pretreatment process] The oxide containing Sm and Fe used in the pretreatment step may be prepared, for example, by mixing Sm oxide and Fe oxide. However, it is preferable to produce the oxide containing Sm and Fe by a step of mixing a solution containing Sm and Fe with a precipitant to obtain a precipitate containing Sm and Fe (precipitation step), and a step of calcining the precipitate to obtain an oxide containing Sm and Fe (oxidation step).

[0011] [Precipitation process] In the precipitation process, the Sm and Fe raw materials are dissolved in a strongly acidic solution to prepare a solution containing Sm and Fe. 17 When N3 is obtained as the main phase, the molar ratio of Sm and Fe (Sm:Fe) is preferably 1.5:17 to 3.0:17, more preferably 2.0:17 to 2.5:17. Raw materials such as La, W, Co, Ti, Sc, Y, Pr, Nd, Pm, Gd, Tb, Dy, Ho, Er, Tm, and Lu may be added to the above-mentioned solution. In terms of residual magnetic flux density, it is preferable to contain La. In terms of coercivity and squareness ratio, it is preferable to contain W. In terms of temperature characteristics, it is preferable to contain Co and Ti.

[0012] The Sm raw material and the Fe raw material are not limited as long as they can be dissolved in a strong acidic solution. For example, in terms of ease of availability, the Sm raw material may be samarium oxide, and the Fe raw material may be FeSO4. The concentration of the solution containing Sm and Fe may be appropriately adjusted within a range in which the Sm raw material and the Fe raw material are substantially dissolved in the acidic solution. In terms of solubility, the acidic solution may be sulfuric acid.

[0013] By reacting the solution containing Sm and Fe with a precipitant, an insoluble precipitate containing Sm and Fe is obtained. Here, the solution containing Sm and Fe may be a solution containing Sm and Fe when reacted with the precipitant. For example, raw materials containing Sm and Fe may be prepared as separate solutions, and each solution may be dropped to react with the precipitant. Even when preparing them as separate solutions, each raw material is appropriately adjusted to a range in which it is substantially soluble in the acidic solution. The precipitant is not limited as long as it is an alkaline solution that reacts with the solution containing Sm and Fe to obtain a precipitate, and examples of the precipitant include ammonia water and caustic soda, with caustic soda being preferred.

[0014] The precipitation reaction is preferably carried out by dropping a solution containing Sm and Fe and a precipitant into a solvent such as water, from the viewpoint of easily adjusting the properties of the precipitate particles. By appropriately controlling the supply rate of the solution containing Sm and Fe and the precipitant, the reaction temperature, the concentration of the reaction solution, the pH during the reaction, etc., a precipitate having a uniform distribution of the constituent elements, a narrow particle size distribution, and a regular powder shape can be obtained. By using such a precipitate, the magnetic properties of the final product, the magnetic powder, are improved. The reaction temperature can be set to 0°C or higher and 50°C or lower, and preferably 35°C or higher and 45°C or lower. The reaction solution concentration is preferably 0.65 mol / L or higher and 0.85 mol / L or lower, and more preferably 0.7 mol / L or higher and 0.85 mol / L or lower, in terms of the total concentration of metal ions. The reaction pH is preferably 5 to 9, and more preferably 6.5 to 8.

[0015] The solution containing Sm and Fe preferably further contains one or more metals selected from the group consisting of La, W, Co and Ti in terms of magnetic properties. For example, it is preferable to contain La in terms of residual magnetic flux density, it is preferable to contain W in terms of coercivity, and it is preferable to contain Co and Ti in terms of temperature properties. The La raw material is not limited as long as it can be dissolved in a strongly acidic solution, and examples of the La raw material include La2O3 and LaCl3 in terms of ease of availability. The La raw material, W raw material, Co raw material and Ti raw material are appropriately adjusted to a range in which they are substantially dissolved in the acidic solution together with the Sm raw material and the Fe raw material, and sulfuric acid is used as the acidic solution in terms of solubility. The W raw material includes ammonium tungstate, the Co raw material includes cobalt sulfate, and the titanium raw material includes titania sulfate.

[0016] When the solution containing Sm and Fe further contains one or more metals selected from the group consisting of La, W, Co, and Ti, an insoluble precipitate containing Sm, Fe, and one or more selected from the group consisting of La, W, Co, and Ti is obtained. Here, the solution only needs to contain one or more selected from the group consisting of La, W, Co, and Ti when reacting with the precipitant, and for example, each raw material may be prepared as a separate solution and each solution may be dropped to react with the precipitant, or the solution containing Sm and Fe may be prepared together.

[0017] The powder obtained in the precipitation process determines the powder particle size, powder shape, and particle size distribution of the final magnetic powder. When the particle size of the obtained powder is measured by a laser diffraction type wet particle size distribution meter, it is preferable that the size and distribution of the entire powder is approximately in the range of 0.05 μm to 20 μm, preferably 0.1 μm to 10 μm.

[0018] After separating the precipitate, it is preferable to remove the solvent from the separated material in order to prevent the precipitate from redissolving in the remaining solvent in the heat treatment of the subsequent oxidation step, causing aggregation of the precipitate when the solvent evaporates, or changes in particle size distribution, powder particle size, etc. Specific examples of the method for removing the solvent include a method in which, when water is used as the solvent, the precipitate is dried in an oven at 70°C to 200°C for 5 hours to 12 hours.

[0019] After the precipitation step, a step of separating and washing the resulting precipitate may be included. The washing step is carried out so that the conductivity of the supernatant solution is 5 mS / m 2 The process is appropriately continued until the following is reached: In the step of separating the precipitate, for example, a solvent (preferably water) can be added to the obtained precipitate and mixed, followed by filtration, decantation, or the like.

[0020] [Oxidation process] The oxidation step is a step of obtaining an oxide containing Sm and Fe by firing the precipitate formed in the precipitation step. For example, the precipitate can be converted into an oxide by heat treatment. When the precipitate is heat treated, it must be performed in the presence of oxygen, for example, in an air atmosphere. In addition, since it must be performed in the presence of oxygen, it is preferable that the nonmetallic part in the precipitate contains oxygen atoms.

[0021] The heat treatment temperature in the oxidation step (hereinafter, oxidation temperature) is not particularly limited, but is preferably 700° C. to 1300° C., and more preferably 900° C. to 1200° C. If the temperature is less than 700° C., the oxidation is insufficient, and if the temperature exceeds 1300° C., the desired shape, average particle size, and particle size distribution of the magnetic powder tend not to be obtained. The heat treatment time is also not particularly limited, but is preferably 1 hour to 3 hours.

[0022] The oxide particles obtained are oxide particles in which Sm and iron are thoroughly mixed microscopically and which reflect the shape, particle size distribution, etc. of the precipitate.

[0023] [Pretreatment process] The pretreatment step is a step in which the above-mentioned oxide containing Sm and Fe is heat-treated in an atmosphere containing a reducing gas to obtain a partial oxide in which a part of the oxide is reduced.

[0024] Here, the partial oxide refers to an oxide in which a part of an oxide is reduced. The oxygen concentration of the partial oxide is not particularly limited, but is preferably 10% by mass or less, and more preferably 8% by mass or less. If it exceeds 10% by mass, the reduction heat generated by Ca in the reduction step increases, and the firing temperature increases, which tends to result in particles that have undergone abnormal particle growth. Here, the oxygen concentration of the partial oxide can be measured by non-dispersive infrared absorption (ND-IR).

[0025] The reducing gas is appropriately selected from hydrocarbon gases such as hydrogen (H2), carbon monoxide (CO), and methane (CH4), but hydrogen gas is preferable from the viewpoint of cost, and the flow rate of the gas is appropriately adjusted within a range in which oxides do not scatter. The heat treatment temperature in the pretreatment step (hereinafter, pretreatment temperature) is preferably 300°C or more and 950°C or less, and the lower limit is more preferably 400°C or more, and even more preferably 750°C or more. The upper limit is more preferably less than 900°C. When the pretreatment temperature is 300°C or more, the reduction of oxides containing Sm and Fe proceeds efficiently. Also, when the temperature is 950°C or less, particle growth and segregation of oxide particles are suppressed, and the desired particle diameter can be maintained. The heat treatment time is not particularly limited, but can be 1 hour or more and 50 hours or less. When hydrogen is used as the reducing gas, it is preferable to adjust the thickness of the oxide layer to 20 mm or less and further adjust the dew point in the reaction furnace to -10°C or less.

[0026] [Reduction process] The reduction step is a step of obtaining alloy particles by heat treating the partial oxide in the presence of a reducing agent, for example, by contacting the partial oxide with calcium melt or calcium vapor. From the viewpoint of magnetic properties, the heat treatment temperature is preferably 920°C or more and 1200°C or less, more preferably 950°C or more and 1150°C or less, and even more preferably 980°C or more and 1100°C or less.

[0027] As a heat treatment different from the above-mentioned heat treatment in the reduction step, a heat treatment may be performed at a first temperature of 1000°C or more and 1090°C or less, and then at a second temperature of 980°C or more and 1070°C or less, which is lower than the first temperature. The first temperature is preferably 1010°C or more and 1080°C or less, and the second temperature is preferably 990°C or more and 1060°C or less. The temperature difference between the first temperature and the second temperature is preferably such that the second temperature is lower than the first temperature by 15°C or more and 60°C or less, and more preferably by 15°C or more and 30°C or less. The heat treatment at the first temperature and the heat treatment at the second temperature may be performed continuously, and a heat treatment at a temperature lower than the second temperature may be included between these heat treatments, but it is preferable to perform them continuously from the viewpoint of productivity. The time of each heat treatment is preferably less than 120 minutes, more preferably less than 90 minutes, from the viewpoint of performing the reduction reaction more uniformly, and the lower limit of the heat treatment time is preferably 10 minutes or more, more preferably 30 minutes or more.

[0028] Metallic calcium, which is a reducing agent, is used in the form of granules or powder, and the particle size is preferably 10 mm or less. This makes it possible to more effectively suppress aggregation during the reduction reaction. Metallic calcium is preferably added in an amount of 1.1 to 3.0 times the reaction equivalent (the stoichiometric amount required to reduce the rare earth oxide, and if the Fe component is in the form of an oxide, includes the amount required to reduce it), and more preferably in an amount of 1.5 to 2.5 times.

[0029] In the reduction step, a disintegration promoter can be used as necessary together with the reducing agent, metallic calcium. The disintegration promoter is used as appropriate to promote disintegration and granulation of the product in the water washing step described below, and examples of the disintegration promoter include alkaline earth metal salts such as calcium chloride and alkaline earth oxides such as calcium oxide. These disintegration promoters are used in a ratio of 1% by mass to 30% by mass, preferably 5% by mass to 30% by mass, based on the samarium oxide.

[0030] [Nitriding process] The nitriding step is a step of obtaining anisotropic magnetic particles by heat-treating the alloy particles obtained in the reduction step in a nitrogen or ammonia-containing atmosphere at a first temperature of 400°C to 470°C, and then heat-treating them at a second temperature of 480°C to 610°C to obtain anisotropic magnetic particles. Since the particulate precipitate obtained in the precipitation step is used, the alloy particles in the form of porous aggregates are obtained in the reduction step. This allows the alloy particles to be heat-treated and nitrided immediately in a nitrogen atmosphere without pulverization, so that the nitriding can be performed uniformly. If the alloy particles are heat-treated at a high second temperature without nitriding at the first temperature, the nitriding process will proceed rapidly, causing abnormal heat generation, which may cause SmFeN to decompose and greatly reduce the magnetic properties. In addition, the atmosphere in the nitriding step is preferably a substantially nitrogen-containing atmosphere, since the nitriding process can slow down the progress of nitriding. The term "substantially" used here is used in consideration of the fact that elements other than nitrogen are inevitably included due to the inclusion of impurities, etc., and for example, the ratio of nitrogen in the atmosphere is 95% or more, preferably 97% or more, and more preferably 99% or more.

[0031] The first temperature in the nitriding step is 400°C or more and 470°C or less, but preferably 410°C or more and 450°C or less. If it is less than 400°C, the nitriding proceeds very slowly, and if it exceeds 470°C, over-nitriding or decomposition is likely to occur due to heat generation. The heat treatment time at the first temperature is not particularly limited, but is preferably 1 hour or more and 40 hours or less, and more preferably 20 hours or less. If it is less than 1 hour, the nitriding may not proceed sufficiently, and if it exceeds 40 hours, the productivity will be poor.

[0032] The second temperature is 480°C or more and 610°C or less, but preferably 500°C or more and 550°C or less. If the temperature is less than 480°C, nitriding may not proceed sufficiently if the particles are large, and if the temperature exceeds 610°C, over-nitriding or decomposition is likely to occur. The heat treatment time at the second temperature is preferably 15 minutes to 5 hours, and more preferably 30 minutes to 2 hours. If the temperature is less than 15 minutes, nitriding may not proceed sufficiently, and if the temperature exceeds 5 hours, productivity will decrease.

[0033] The heat treatment at the first temperature and the heat treatment at the second temperature may be carried out continuously, and a heat treatment at a temperature lower than the second temperature may be included between these heat treatments. However, from the viewpoint of productivity, it is preferable to carry out the heat treatments continuously.

[0034] [Post-processing process] The product obtained after the nitriding step contains, in addition to the magnetic particles, by-produced CaO, unreacted metallic calcium, etc., and these may be in the form of a composite sintered lump. The product obtained after the nitriding step can be put into cooling water, and the CaO and metallic calcium can be separated from the magnetic powder as a calcium hydroxide (Ca(OH)2) suspension. Furthermore, the remaining calcium hydroxide may be sufficiently removed by washing the magnetic powder with acetic acid or the like. When the product is put into water, the oxidation of metallic calcium by water and the hydration reaction of the by-produced CaO cause the composite sintered lump-like reaction product to disintegrate, i.e., to become fine powder.

[0035] [Alkaline treatment process] The product obtained after the nitriding step may be put into an alkaline solution. Examples of the alkaline solution used in the alkaline treatment step include an aqueous calcium hydroxide solution, an aqueous sodium hydroxide solution, and an aqueous ammonia solution. Among these, an aqueous calcium hydroxide solution and an aqueous sodium hydroxide solution are preferred in terms of wastewater treatment and high pH. The alkaline treatment of the product leaves an Sm-rich layer containing a certain amount of oxygen, which functions as a protective layer, thereby suppressing an increase in oxygen concentration due to the alkaline treatment.

[0036] The pH of the alkaline solution used in the alkaline treatment step is not particularly limited, but is preferably at least 9, and more preferably at least 10. If the pH is less than 9, the reaction rate in forming calcium hydroxide is fast and heat generation is large, so that the oxygen concentration in the finally obtained anisotropic magnetic powder tends to be high.

[0037] In the alkaline treatment step, the moisture content of the magnetic powder obtained after treatment with the alkaline solution can be reduced by a method such as decantation, if necessary.

[0038] [Acid treatment process] The alkaline treatment step may be followed by an acid treatment step in which the magnetic powder is treated with an acid. In the acid treatment step, at least a portion of the Sm-rich layer is removed to reduce the oxygen concentration in the magnetic powder as a whole. In addition, in the manufacturing method according to the embodiment of the present invention, since no pulverization or the like is performed, the anisotropic magnetic powder has a small average particle size, a narrow particle size distribution, and does not contain fine powder generated by pulverization or the like, so that it is possible to suppress an increase in the oxygen concentration.

[0039] The acid used in the acid treatment step is not particularly limited, and examples thereof include hydrogen chloride, nitric acid, sulfuric acid, acetic acid, etc. Among these, hydrogen chloride and nitric acid are preferred since they do not leave impurities behind.

[0040] The amount of acid used in the acid treatment step is preferably 3.5 parts by mass or more and 13.5 parts by mass or less, more preferably 4 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of magnetic powder. If it is less than 3.5 parts by mass, oxides remain on the surface of the magnetic powder, and the oxygen concentration becomes high. If it exceeds 13.5 parts by mass, reoxidation is likely to occur when exposed to the atmosphere, and the magnetic powder is dissolved, so the cost tends to be high. By setting the amount of acid to 3.5 parts by mass or more and 13.5 parts by mass or less relative to 100 parts by mass of magnetic powder, it is possible to make the magnetic powder surface covered with an Sm-rich layer oxidized to such an extent that reoxidation is unlikely to occur when exposed to the atmosphere after acid treatment, so that an anisotropic magnetic powder with a low oxygen concentration, a small average particle size, and a narrow particle size distribution can be obtained.

[0041] In the acid treatment step, the moisture content of the magnetic powder obtained after the acid treatment can be reduced by a method such as decantation, if necessary.

[0042] [Dehydration process] It is preferable to include a dehydration step after the acid treatment step. The dehydration step reduces the moisture content in the solid content before vacuum drying, and suppresses the progress of oxidation during drying that occurs when the solid content before vacuum drying contains more moisture. Here, the dehydration step means a process in which pressure or centrifugal force is applied to reduce the moisture content of the solid content after treatment compared to the solid content before treatment, and does not include simple decantation, filtration, or drying. The dehydration method is not particularly limited, but examples include squeezing, centrifugation, and the like.

[0043] The amount of moisture contained in the magnetic powder after the dehydration treatment is not particularly limited, but from the viewpoint of suppressing the progress of oxidation, it is preferably 13% by mass or less, and more preferably 10% by mass or less.

[0044] The magnetic powder obtained by the acid treatment, or the magnetic powder obtained by the acid treatment followed by the dehydration treatment, is preferably vacuum dried. The drying temperature is not particularly limited, but is preferably 70° C. or higher, and more preferably 75° C. or higher. The drying time is also not particularly limited, but is preferably 1 hour or longer, and more preferably 3 hours or longer.

[0045] [Surface treatment process] The magnetic powder obtained in the post-treatment process may be subjected to a surface treatment. For example, a phosphoric acid solution is added as a surface treatment agent in an amount of 0.10 to 10 wt% as PO4 relative to the magnetic particle solid content obtained in the nitriding process. The magnetic powder is then appropriately separated from the solution and dried to obtain a surface-treated magnetic powder.

[0046] The anisotropic magnetic powder according to one embodiment of the present invention comprises: The average particle size measured under dry conditions using a laser diffraction particle size distribution analyzer is 2 μm or more and 6 μm or less, and is calculated using the following formula: Span = (D90-D10) / D50 (Here, D10, D50, and D90 are particle sizes corresponding to 10%, 50%, and 90% of the integrated value of the particle size distribution based on volume, respectively.) The span defined by is 1.6 or less, Contains Sm, Fe, La, and N. The N content is 3.3 mass% or more and 3.5 mass% or less, The residual magnetization σr is 145 emu / g or more.

[0047] The anisotropic magnetic powder in this embodiment can be produced, for example, by the manufacturing method described above, but because the magnetic powder is not mechanically crushed by grinding or the like, the anisotropic magnetic powder has a low oxygen concentration, a small average particle diameter, a narrow particle size distribution (small span), and a high residual magnetic flux density.

[0048] The anisotropic magnetic powder in this embodiment is typically represented by the following general formula: Sm v Fe (100-v―w-x-y-z-u) N w La x W y Co z Ti u (In the formula, 3≦v≦30, 5≦w≦15, 0.1≦x≦0.3, 0≦y≦2.5, 0≦z≦2.5, and 0≦u≦2.5.) It is expressed as:

[0049] In the general formula, v is specified to be between 3 and 30 because, if it is less than 3, the unreacted portion of the iron component (α-Fe phase) separates, reducing the coercive force of the magnetic powder and making it no longer a practical magnet, and if it exceeds 30, Sm elements precipitate, making the magnetic powder unstable in the air and reducing the residual magnetic flux density. Also, w is specified to be between 5 and 15 because, if it is less than 5, almost no coercive force can be expressed, and if it exceeds 15, nitrides of Sm and iron itself are formed.

[0050] When La is contained, the La content is preferably from 0.1 mass % to 5 mass %, and more preferably from 0.15 mass % to 1 mass %, in terms of residual magnetic flux density.

[0051] When W is contained, the content of W is preferably from 0.1% by mass to 5% by mass, and more preferably from 0.15% by mass to 1% by mass, from the viewpoint of coercive force.

[0052] When Co is contained, the Co content is preferably from 0.1 mass % to 5 mass %, and more preferably from 0.15 mass % to 1 mass %, in terms of temperature characteristics.

[0053] When Ti is contained, the Ti content is preferably from 0.1 mass % to 5 mass %, and more preferably from 0.15 mass % to 1 mass %, from the viewpoint of temperature characteristics.

[0054] The content of N is preferably 3.3 mass % or more and 3.5 mass % or less. If it exceeds 3.5 mass %, over-nitriding occurs, whereas if it is less than 3.3 mass %, nitriding becomes insufficient and the magnetic properties tend to deteriorate.

[0055] The average particle size of the anisotropic magnetic powder is 2 μm or more and 6 μm or less, preferably 3 μm or more and 6 μm or less, and more preferably 4 μm or more and 6 μm or less. If it is less than 2 μm, the surface area is large and oxidation is likely to occur, and if it exceeds 6 μm, the magnetic powder has a multi-domain structure, which tends to deteriorate the magnetic properties. Here, the average particle size means the particle size measured under dry conditions using a laser diffraction type particle size distribution measuring device.

[0056] The anisotropic magnetic powder has the following formula: Span = (D90-D10) / D50 (Here, D10, D50, and D90 are particle sizes corresponding to 10%, 50%, and 90% of the integrated value of the particle size distribution based on volume, respectively.) The span defined by is 1.6 or less, preferably 1.3 or less. If it exceeds 1.6, large particles are present and the magnetic properties tend to deteriorate.

[0057] The average circularity of the magnetic powder is preferably 0.50 or more, more preferably 0.70 or more, and particularly preferably 0.75 or more. When the circularity falls below 0.50, the flowability is deteriorated, and stress is applied between particles during magnetic field molding, resulting in a deterioration of magnetic properties. A scanning electron microscope (SEM) is used to measure the circularity, and Particle Analysis Ver. 3 by Sumitomo Metal Technology is used as image analysis software. SEM images taken at 3000x are binarized by image processing, and the circularity of each particle is determined. The circularity defined in the present invention means the average circularity obtained by measuring approximately 1000 to 10000 particles. In general, the circularity increases as the number of particles with a smaller particle diameter increases, so the circularity was measured for particles of 1 μm or more. The circularity was measured using the following formula: circularity=(4πS / L 2 ) is used, where S is the two-dimensional projected area of ​​the particle, and L is the two-dimensional projected perimeter.

[0058] The residual magnetization σr of the magnetic powder is preferably 145 emu / g or more, more preferably 147 emu / g or more. The saturation magnetization σm is preferably 148 emu / g or more, more preferably 150 emu / g or more. Furthermore, σr / σm is preferably 0.96 or more, more preferably 0.98 or more.

[0059] The anisotropic magnetic powder of this embodiment has high remanent magnetization and can therefore be used, for example, as a sintered magnet or a bonded magnet.

[0060] The bonded magnet is made from the anisotropic magnetic powder of this embodiment and a resin. By including this anisotropic magnetic powder, a composite material with high magnetic properties can be formed.

[0061] The resin contained in the composite material may be either a thermosetting resin or a thermoplastic resin, but is preferably a thermoplastic resin. Specific examples of the thermoplastic resin include polyphenylene sulfide resin (PPS), polyether ether ketone (PEEK), liquid crystal polymer (LCP), polyamide (PA), polypropylene (PP), polyethylene (PE), etc.

[0062] When obtaining a composite material, the weight ratio of the anisotropic magnetic powder to the resin (resin / magnetic powder) is preferably 0.10 to 0.15, and more preferably 0.11 to 0.14.

[0063] The composite material can be obtained, for example, by mixing anisotropic magnetic powder and a resin at 280 to 330° C. using a kneader.

[0064] By using the composite material, it is possible to manufacture a bonded magnet. Specifically, for example, the composite material is heat-treated while aligning the easy magnetization domains in an orienting magnetic field (orientation process), and then pulse-magnetized in a magnetizing magnetic field (magnetization process) to obtain a bonded magnet.

[0065] The heat treatment temperature in the orientation step is preferably, for example, 90 to 200° C., and more preferably 100 to 150° C. The magnitude of the orientation magnetic field in the orientation step can be, for example, 720 kA / m. The magnitude of the magnetizing magnetic field in the magnetizing step can be, for example, 1500 to 2500 kA / m.

[0066] The sintered magnet is produced by molding and sintering the anisotropic magnetic powder of the present embodiment. The anisotropic magnetic powder of the present embodiment has a low oxygen concentration, a small average particle size, a narrow particle size distribution, and a high residual magnetic flux density, making it suitable for sintered magnets.

[0067] As described in JP 2017-055072 A, for example, sintered magnets are produced by sintering magnetic powder in an atmosphere with an oxygen concentration of 0.5 volume ppm or less, at a temperature of more than 300°C and less than 600°C, and under a pressure of 1000 MPa or more and 1500 MPa or less.

[0068] As described in, for example, WO 2015 / 199096, a sintered magnet is produced by pre-compressing a magnetic powder in a magnetic field of 6 kOe or more, and then warm compaction molding at a temperature of 600°C or less and a molding surface pressure of 1 to 5 GPa.

[0069] As described in JP 2016-082175 A, for example, a sintered magnet is produced by cold compacting a mixture containing a magnetic powder and a metal binder at a molding surface pressure of 1 to 5 GPa, and then heating the mixture at a temperature of 350 to 600°C for 1 to 120 minutes. EXAMPLES

[0070] Examples will be described below. Unless otherwise specified, "%" is by weight.

[0071] [evaluation] The content of each metal, the nitrogen concentration, the average particle size, the particle size distribution, the residual magnetization σr, and the saturation magnetization σm were evaluated by the following methods.

[0072] <Content of each metal> The content of each metal (Sm, Fe, La, Co, etc.) was measured by dissolving in hydrochloric acid and using ICP-AES (instrument name: Optima8300). <Nitrogen concentration> The nitrogen concentration was measured by a thermal conductivity method (EMGA-820 manufactured by Horiba, Ltd.).

[0073] <Average particle size and particle size distribution> The average particle size and particle size distribution were measured using a laser diffraction particle size distribution measuring device (HELOS&RODOS, manufactured by Japan Laser Co., Ltd.).

[0074] <Residual magnetization σr, saturation magnetization σm> The magnetic powder obtained was packed in a sample container together with paraffin wax, and the paraffin wax was melted in a dryer, after which the easy magnetization domains were aligned in an aligning magnetic field of 16 kA / m. The magnetically oriented sample was pulse-magnetized in a magnetizing magnetic field of 32 kA / m, and the residual magnetization σr and saturation magnetization σm were measured using a VSM (vibrating sample magnetometer) with a maximum magnetic field of 16 kA / m.

[0075] Manufacturing Example 1 5.0 kg of FeSO4·7H2O was mixed and dissolved in 2.0 kg of pure water. 0.49 kg of Sm2O3 and 0.74 kg of 70% sulfuric acid were then added and thoroughly stirred to completely dissolve. Pure water was then added to the resulting solution, and the final Fe concentration was adjusted to 0.726 mol / L and the Sm concentration to 0.112 mol / L to create a SmFe sulfuric acid solution.

[0076] [Precipitation process] The entire amount of the prepared SmFe sulfate solution was dropped into 20 kg of pure water kept at a temperature of 40°C for 70 minutes from the start of the reaction while stirring, and at the same time, 15% ammonia solution was dropped to adjust the pH to 7 to 8. This resulted in a slurry containing SmFe hydroxide. The obtained slurry was washed with pure water by decantation, and the hydroxide was subjected to solid-liquid separation. The separated hydroxide was dried in an oven at 100°C for 10 hours.

[0077] [Oxidation process] The hydroxide obtained in the precipitation process was calcined in air at 1000°C for 1 hour. After cooling, red SmFe oxide was obtained as raw powder.

[0078] Manufacturing Example 2 The same procedure as in Production Example 1 was carried out except that 0.035 kg of La2O3 was added, thereby obtaining a red SmFeLa oxide.

[0079] Production Example 3 A red SmFeLaCo oxide was obtained in the same manner as in Production Example 1, except that 0.071 kg of 31.8% LaCl and 0.015 kg of 20.8% cobalt sulfate were added.

[0080] Example 1 [Pretreatment process] 100 g of the SmFe oxide obtained in Production Example 1 was placed in a steel container so that the bulk thickness was 10 mm. The container was placed in a furnace, and after reducing the pressure to 100 Pa, the temperature was raised to the pretreatment temperature of 850°C while introducing hydrogen gas, and the temperature was maintained for 15 hours. The oxygen concentration was measured by a non-dispersive infrared absorption method (ND-IR) (EMGA-820 manufactured by Horiba, Ltd.) and found to be 5 mass%. This revealed that the oxygen bonded to Sm was not reduced, and 95% of the oxygen bonded to Fe was reduced to obtain a black partial oxide.

[0081] [Reduction process] 60 g of the partial oxide obtained in the pretreatment step and 19.2 g of metallic calcium having an average particle size of about 6 mm were mixed and placed in a furnace. After evacuating the furnace, argon gas (Ar gas) was introduced. The temperature was raised to a first temperature of 1045°C and held for 45 minutes, and then cooled to a second temperature of 1000°C and held for 30 minutes to obtain SmFe alloy particles.

[0082] [Nitriding process] Subsequently, the temperature inside the furnace was cooled to 100°C, and then the furnace was evacuated to a vacuum, and while introducing nitrogen gas, the temperature was raised to a first temperature of 430°C and held for 3 hours, and then the temperature was raised to a second temperature of 500°C and held for 1 hour, and then cooled to obtain an aggregated product containing magnetic particles.

[0083] [Post-processing process] The aggregated product obtained in the nitriding step was poured into 3 kg of pure water and stirred for 30 minutes. After standing, the supernatant was drained by decantation. The process of pouring into pure water, stirring and decantation was repeated 10 times. Next, 2.5 g of 99.9% acetic acid was poured into the product and stirred for 15 minutes. After standing, the supernatant was drained by decantation. The process of pouring into pure water, stirring and decantation was repeated twice.

[0084] [Surface treatment process] A phosphoric acid solution was added to the resulting slurry. The phosphoric acid solution was added in an amount of 1 wt% as PO4 relative to the magnetic particle solid content. After stirring for 5 minutes, solid-liquid separation was performed, followed by vacuum drying at 80°C for 3 hours to obtain magnetic powder. The content and composition of the obtained magnetic powder are shown in Table 1. The composition was calculated from the content of each metal and nitrogen analysis.

[0085] Example 2 The same procedure as in Example 1 was carried out except that the second temperature in the nitriding step was changed to 520°C.

[0086] Comparative Example 1 The same procedure as in Example 1 was carried out, except that in the nitriding step, the first temperature was raised to 430° C., held for 3 hours, and then cooled to obtain an aggregate product containing magnetic particles.

[0087] The residual magnetization σr, nitrogen concentration, and particle size distribution were measured by the above-mentioned methods using the magnetic powders obtained in Examples 1 and 2 and Comparative Example 1. The evaluation results are shown in Table 2.

[0088] [Table 1]

[0089] [Table 2]

[0090] From the results in Table 2, in Examples 1 and 2, when nitriding was performed at 430°C and then at 500°C or 520°C, the nitrogen concentration increased and the residual magnetization σr became higher than in Comparative Example 1.

[0091] Example 3 The same procedure as in Example 1 was carried out except for using the SmFeLa oxide obtained in Production Example 2. The contents and compositional formulas of the obtained magnetic powder are shown in Table 3.

[0092] Example 4 The same procedure as in Example 3 was carried out except that the second temperature in the nitriding step was changed to 520°C.

[0093] Example 5 The same procedure as in Example 3 was carried out except that the second temperature in the nitriding step was changed to 550°C.

[0094] Example 6 The same procedure as in Example 3 was carried out except that the second temperature in the nitriding step was changed to 600°C.

[0095] Comparative Example 2 The same procedure as in Example 3 was carried out, except that in the nitriding step, the first temperature was raised to 430° C., held for 3 hours, and then cooled to obtain an aggregate product containing magnetic particles.

[0096] The residual magnetization σr, nitrogen concentration, and particle size distribution were measured by the above-mentioned methods using the magnetic powders obtained in Examples 3 to 6 and Comparative Example 2. The evaluation results are shown in Table 4.

[0097] [Table 3]

[0098] [Table 4]

[0099] From the results in Table 4, in Examples 3 to 6, even when the magnetic powders had a larger average particle size than those in Examples 1 and 2, when they were nitrided at 430°C and then at 500 to 600°C, the nitrogen concentration increased compared to Comparative Example 2. The residual magnetization σr was even higher than in Examples 1 and 2.

[0100] Example 7 The same procedure was carried out as in Example 1, except that the SmFeLaCo oxide obtained in Production Example 3 was used. The contents and compositional formulas of the obtained magnetic powder are shown in Table 5.

[0101] Example 8 The same procedure as in Example 7 was carried out except that the second temperature in the nitriding step in Example 7 was changed to 520°C.

[0102] Example 9 The same procedure as in Example 7 was carried out except that the second temperature in the nitriding step in Example 7 was changed to 550°C.

[0103] Example 10 The same procedure as in Example 7 was carried out except that the second temperature in the nitriding step in Example 7 was changed to 600°C.

[0104] Comparative Example 3 The same procedure as in Example 7 was carried out, except that in the nitriding step, the first temperature was raised to 430° C., held for 3 hours, and then cooled to obtain an aggregate product containing magnetic particles.

[0105] The residual magnetization σr, nitrogen concentration, and particle size distribution were measured by the above-mentioned methods using the magnetic powders obtained in Examples 7 to 10 and Comparative Example 3. The evaluation results are shown in Table 6.

[0106] [Table 5]

[0107] [Table 6]

[0108] From the results in Table 6, in Examples 7 to 9, even when the magnetic powders having a larger average particle size than those of Examples 1 and 2 were nitrided at 500 to 600°C after nitriding at 430°C, the nitrogen concentration increased compared to Comparative Example 3. The residual magnetization σr was even higher than that of Examples 1 and 2. [Industrial Applicability]

[0109] The anisotropic magnetic powder obtained by the manufacturing method of the present invention has a small average particle size, a narrow particle size distribution, and a high remanent magnetization σr, and is therefore particularly suitable for use in bonded magnets.

Claims

1. A pretreatment step of obtaining a partial oxide by heat-treating an oxide containing Sm and Fe in an atmosphere containing a reducing gas; heat treating the partial oxide in the presence of a reducing agent to obtain alloy particles; and A step of heat-treating the alloy particles at a first temperature of 400° C. to 470° C. in a nitrogen or ammonia-containing atmosphere, and then heat-treating the alloy particles at a second temperature of 480° C. to 610° C. to obtain a nitride. A method for producing an anisotropic magnetic powder comprising the steps of:

2. 2. The method for producing an anisotropic magnetic powder according to claim 1, wherein the oxide containing Sm and Fe further contains La.

3. 3. The method for producing an anisotropic magnetic powder according to claim 1, wherein the oxide containing Sm and Fe further contains at least one selected from the group consisting of Co, W, and Ti.

Citation Information

Patent Citations

  • Production of r2t17 alloy powder, production of r2t17nx type magnet powder, and high pressure heat treatment equipment

    JP1996013006A

  • Rare earth-transition metal-nitrogen magnet powder, method for producing the same, composition for bond magnet using the same, and bond magnet

    JP2011219819A

  • Anisotropic magnetic powder and production method therefor

    JP2017117937A

  • Samarium-iron-nitrogen based sintered magnet, and manufacturing method of samarium-iron-nitrogen based sintered magnet

    JP2017055072A

  • Manufacturing method of anisotropic magnetic powder

    JP2019112716A